Advanced adenocarcinoma of terminal ileum: an unusual neoplasmrevealed by an unusual diagnostic tool - Nocchiero, M.C.; Verderosa, G.; Muscatiello et al., N. (Acta Biomedica Atenei Parmensis, 2011)
Background and aim: Terminal ileum adenocarcinoma is a rare tumour. Its incidence or prevalence among the other sites of gastro-intestinal tract is unknown, since it has been only sporadically described. Since contrast enhanced ultrasonography has been recently used to study bowel alterations in the course of neoplastic or inflammatory disorders, we report here a case of a rare tumour (terminal ileum poorly differentiated adenocarcinoma) in which the investigation played a pivotal role to obtain a defined diagnosis. Materials and methods (case report): Here we report the case of a 62 year old male patient. Due to intestinal occlusive symptoms and body weight decrease of about 8 Kg, he performed an abdominal computed tomography, intestinal magnetic resonance with double contrast medium, colonoscopy and contrast enhanced ultrasonography using a second generation medium. Results: In our case the peculiar aspect is that no arterial enhancement was observed and the finding remained unchanged for about 2.48 minutes as well as after a further administration of 1.5 ml of contrast medium. This aspect was not suggestive of an active inflammation such as Crohn’s disease, where a marked contrast medium enhancement should be expected. Conclusions: At present it is too speculative to emphasize contrast enhanced ultrasonography as usefulness tool in the diagnosis of terminal ileum tumors. Nevertheless, our preliminary experience strongly encourages the diffusion of the method.